IMPLEMENTATION OF BUSINESS INTELLIGENCE ON BANKING, RETAIL, AND EDUCATIONAL INDUSTRY - Arta Moro Sundjaja (Bina Nusantara University, 2013)
Information technology is useful to automate business process involving considerable data transaction in the daily basis. Currently, companies have to tackle large data transaction which is difficult to be handled manually. It is very difficult for a person to manually extract useful information from a large data set despite of the fact that the information may be useful in decision-making process. This article studied and explored the implementation of business intelligence in banking, retail, and educational industries. The article begins with the exposition of business intelligence role in the industries; is followed by an illustration of business intelligence in the industries and finalized with the implication of business intelligence implementation.